Topical Scar Treatment Products for Wounds: A Systematic Review. Issue 12 (December 2020) - Tran, Benjamin; Wu, Jashin J.; Ratner, Desiree; Han, George
Abstract : BACKGROUND: There is an increasing number of over-the-counter topical products that are said to prevent pathologic scar formation and improve scar cosmesis. However, robust clinical data are lacking to substantiate these claims and to guide selection of topical products. OBJECTIVE: To determine the effectiveness of topical scar management products, including silicone gel, Allium cepa onion extract, vitamin E, trolamine, and microporous tape. METHODS AND MATERIALS: A PubMed search (2005–2019) was performed to identify studies of topical scar management products. Randomized controlled trials (RCTs), quasi-RCTs, meta-analyses, and controlled clinical trials were included for analysis. RESULTS: A total of 34 trials were included in this study. Of the 16 trials investigating silicone gel sheets, numerous high-quality RCTs found that silicone gel sheets and silicone gels significantly improved scar outcomes. Only a limited number of studies supported the effectiveness of onion extract, vitamin E, trolamine, and microporous tape products. CONCLUSION: Silicone gel products are an effective noninvasive treatment to prevent formation of pathologic scars and improve mature scars. Further high-quality studies are needed to elucidate the long-term effectiveness of these therapies. Abstract : Supplemental Digital Content is Available in the Text.